Enhancing Historical Understanding through Local Wisdom Based Learning: A Case Study in Senior High Schools - Firmansyah, Haris; Ramadhan, Iwan; Wiyono, Hadi (Universitas Negeri Padang, 2025)
In the growing concern over students’ detachment from historical content and the weakening of cultural identity, contextualizing history education through local wisdom emerges as a pedagogical imperative. This study explores how integrating local wisdom into history education can enhance student engagement, historical comprehension, and emotional connection to the subject at SMA N Kota Pontianak. Using a qualitative case study approach, data were collected through classroom observations, teacher interviews, and student reflections. The results demonstrate that local wisdom-based learning enriches historical understanding by linking curriculum content to students’ cultural heritage through folklore, oral traditions, and community narratives. Students showed increased motivation, active participation, and a stronger emotional bond with historical topics, reinforcing their cultural pride and sense of identity. While aligning with existing research on contextual learning, this study offers a novel contribution by examining the affective dimension of learning and its implementation in a multicultural, local Indonesian context. It highlights the strategic role of teachers in adapting local narratives into history lessons. It underscores the pedagogical value of local wisdom for fostering critical thinking, cultural awareness, and identity-based meaning-making. Despite challenges such as limited teaching resources and diverse interpretations of local traditions, the study concludes that local wisdom-based learning represents a powerful approach to revitalizing history education. It recommends that curriculum developers and educators systematically integrate local wisdom to promote more relevant, reflective, and inclusive learning experiences.